Conversion of HI Molecule to H2 Molecule - Gautam, Arjun Kumar (Himalayan Physics, 2015)
In this article I review the historical development and conversion of atomic to molecular hydrogen in astronomy. I discuss how the discoveries of HI and H2 in the interstellar medium were followed by studies of the relative abundance of atomic and molecular gas. Understanding this led to increasingly sophisticated theoretical models for H2 formation on the surface of interstellar dust grains. In certain situations, astronomical data can be used to constrain the formation rate of H2 molecules. Finally, I use the reasonably well-determined chemistry of HI and H2 to determine the overall timescale of star formation. The Himalayan Physics Vol. 5, No. 5, Nov. 2014 Page: 82-86